2019
DOI: 10.17265/2328-7136/2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality and Acceptability Evaluation of Ogi Flour Biofortified with Garlic and Ginger

Abstract: Ogi an affordable complementary food is of paramount importance due to its popularity as diets of many native African populations. The study explored effects of biofortification with garlic and ginger on acceptability and nutritional quality of ogi flour prepared from sorghum and quality protein maize by natural fermentation technique. Pasting properties, bulk density, water absorption capacity, total reducing sugar and sensory characteristics were evaluated. Biofortified samples showed stable total reducing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Malomo et al (2019) also reported that the total reducing sugar of fermenting maize was higher than that of acha during fermentation. The range of result of this work is in agreement with the report of Olaniran et al (2019). Total sugar in ogi at different stages of fermentation.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Malomo et al (2019) also reported that the total reducing sugar of fermenting maize was higher than that of acha during fermentation. The range of result of this work is in agreement with the report of Olaniran et al (2019). Total sugar in ogi at different stages of fermentation.…”
Section: Resultssupporting
confidence: 92%
“…The cereals (maize, acha and sorghum) were sorted, weighed and steeped separately for 72 h. The grains were drained and wet-milled into slurry using an attrition mill. The ogi (100 ml) obtained was dispensed into sterile plastics and fermented for 48 h (Olaniran et al 2019).…”
Section: Production Of Ogimentioning
confidence: 99%
See 1 more Smart Citation
“…Acha grains were purchased from a local market in Ebonyi State, Nigeria. Ogi was produced from the cereals using the method described by Olaniran et al (2019). Slurries of ogi obtained from these cereals were further fermented for 48 h. Samples were taken from the fermenting slurries at 0, 12, 24, 36 and 48 h. Samples obtained were then used for further studies.…”
Section: Methodsmentioning
confidence: 99%
“…Ginger is a commonly added to beverages for flavor. Garlic (Allium sativum) also regarded as Russian penicillin, stinky rose, tafanuwa in Hausa, ayo-ishi in Igbo and ayu in Yoruba (Neeraj et al, 2014; Olaniran et al, 2019a). Garlic comprises of sulphur containing compounds, the fresh bulb contains allicin, alliin and volatile oil.…”
Section: Introductionmentioning
confidence: 99%